The legitimacy of UN member states - Volker Roben (Coexistence, Cooperation and Solidarity. Liber amicorum Rüdiger Wolfrum, 2 vols, 2011)
Develops standards of legitimacy applicable to states qua their UN membership. Details legal concretisation and enforcement of these standards. Draws implications for analysts and actors.